Method for nanoetching copper and copper alloy surfaces

Through the combined treatment of the prepreg composition and the aqueous etching solution, the problems of linear shape changes and adhesion properties of the surface of nano-etched copper and copper alloys are solved, and the retaining and efficient adhesion properties of rectangular shapes are achieved, reducing signal loss.

CN119213170APending Publication Date: 2024-12-27ATOTECH DEUT GMBH & CO KG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041244.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-17
Filing Date
2023-05-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has problems of linear shape changes, undercuts and line width reduction when nanoetching the surface of copper and copper alloys, and it is difficult to maintain good adhesion between copper and dielectric materials and ultra-low roughness.

Method used

Using the prepreg composition, a combination of sulfur-containing compounds and an etching solution, the copper or copper alloy surface is treated by a non-etching step and an etching step, respectively, to form a nanostructure to prevent the arcing of copper grains and avoid unnecessary copper removal, and Use aqueous etching solution to optimize the etching process.

Benefits of technology

Effectively maintain the rectangular shape of the copper wire, reduce line width changes, enhance the adhesion performance of copper to dielectric materials, reduce high-frequency signal loss, and maintain peel strength in high-acceleration stress tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213170A_ABST
    Figure CN119213170A_ABST
Patent Text Reader

Abstract

The invention provides a method for nanoetching a copper or copper alloy surface, characterized by the following method steps: i) providing a substrate having at least one copper or copper alloy surface, ii) contacting at least a portion of the copper or copper alloy surface with a prepreg composition, iii) contacting at least a portion of the copper or copper alloy surface with an etching solution, the method is characterized in that the steps are carried out in sequence; -step ii) is a non-etching step; -step iii) is an etching step; and-the prepreg composition comprises at least one sulfur-containing compound selected from the list defined in the claims.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for nano-etching copper and copper alloy surfaces. In particular, the present invention relates to a method for nano-etching copper and copper alloy surfaces suitable for manufacturing printed circuit boards, IC substrates, interposers, etc. in the field of the electronics industry. Background Art

[0002] In the manufacture of printed circuit boards, the surface of copper is treated to promote adhesion between the copper surface and the resist before coating the copper surface with a photoresist, solder resist, resin for permanent adhesion, etc. When processing substrates with fine wiring patterns, chemical etching is generally used. When manufacturing multi-layer printed circuit boards, attempts have been made to promote adhesion between the copper conductive patterned layer and the resin layer, for example, by forming an oxide layer on the copper surface and reducing the oxide layer to metallic copper with a reducing agent while maintaining the geometry of the oxide layer.

[0003] The negative circuit pattern is formed by a) applying a resist, such as a polymeric dry film resist or a metal resist, on the copper layer, b) etching away the portions of the copper not covered by the resist, and c) removing the resist from the remaining copper circuitry.

[0004] The etching solution applied for this task is selected from different types of compositions, such as a mixture of an oxidizing agent and an acid. Two main types of etching solutions are based on acids (such as sulfuric acid or hydrochloric acid) and contain hydrogen peroxide, copper ions or iron ions as oxidizing agents. Such etching solutions are disclosed in C. F. Coombs, Jr., "Printed Circuits Handbook", 5th edition, 2001, Chapter 33.4.3, pages 33.14 to 33.15 and Chapter 33.4.5, page 33.17.

[0005] The continued miniaturization of circuits in terms of line width / line space values ​​and the thickness of the copper layer to be etched does not allow the use of conventional etching solutions as described above.

[0006] EP 2 241 653 discloses a composition for micro-etching copper or copper alloys during the manufacture of printed circuit boards. The composition comprises a copper salt, a halide ion source, a buffer system and a benzothiazole compound as an etching optimizer.

[0007] EP 2 754 732 discloses an aqueous composition for etching copper and copper alloys and a process for etching copper and copper alloys using the aqueous composition. The aqueous composition comprises Fe 3+ An ion source, an acid, a triazole or tetrazole derivative, and an etching additive selected from N-alkylated iminodipropionic acid, a salt thereof, a modified polyethylene glycol ether, and a quaternary urea-based polymer.

[0008] WO 2017 / 108513 discloses an aqueous etching solution and method for treating a copper or copper alloy surface. The aqueous solution comprises at least one acid, at least one oxidizing agent suitable for oxidizing copper, at least one halide ion source and at least one polyamide.

[0009] EP 3 034 654 discloses a composition for micro-etching a copper or copper alloy surface, wherein the composition comprises Fe 3+ Ion source, Br - An ion source, an inorganic acid, and a benzothiazole compound as an etch optimizer.

[0010] WO 02 / 04706 discloses an etching solution which is acidic and contains hydrogen peroxide, at least one five-membered nitrogen-containing heterocyclic compound and at least one microstructure modifier selected from the group comprising organic thiols, organic thioethers, organic disulfides and sulfamides.

[0011] If the semi-additive method (SAP, Figure 1 A) to produce copper tracks, then the disadvantages of the known etching methods are even more numerous. Here, a bare dielectric substrate is first coated with a seed layer that acts as a conductive layer. The seed layer comprises copper deposited, for example, by electroless plating. Next, a patterned resist layer is formed on the seed layer, and a thicker second copper layer is deposited on the seed layer by electroplating into the openings of the patterned resist layer. The patterned resist layer is stripped, and a differential etching step is required to remove the seed layer between the copper tracks deposited by electroplating. The seed layer deposited by electroless plating has a finer grain structure than the second copper layer deposited by electroplating. Different grain structures can produce different etching properties of the individual copper layers.

[0012] A similar situation occurs when copper tracks are manufactured by modified semi-additive process (m-SAP) or advanced modified SAP (am-SAP), where a thick second copper layer is deposited in openings of a patterned resist layer on a first thin copper layer. For example, the first copper layer is manufactured by thinning a copper cladding layer connected to a dielectric substrate. Again, both the first and second copper layers have different grain structures.

[0013] The etching solution based on sulfuric acid and hydrogen peroxide causes undesirable undercutting of the first copper layer during etching ( Figure 1 B), which causes insufficient adhesion of the copper layer on the dielectric substrate.

[0014] Etching solutions based on sulfuric acid and iron ions typically exhibit Figure 1The etch properties shown in C. This trapezoidal line shape is undesirable because the wider base of the etched copper line can cause circuit shorts, which is unacceptable. This phenomenon of forming a trapezoidal etch result is referred to herein as "line shape variation."

[0015] Another undesirable side effect of copper etching is usually a reduction in line width. This is usually caused by excessive etching of dissolved copper ions on all surfaces of the copper line being processed (see Figure 1 D).

[0016] Objectives of the invention

[0017] It is therefore an object of the present invention to provide a method for nano-etching copper and copper alloys which overcomes the limitations and disadvantages of the prior art. It is also an object of the present invention to provide a method for etching copper and copper alloys which results in improved retention of the geometry of the copper or copper alloy lines (such as a rectangular line shape) (which can be measured by top-bottom difference) after treatment, less pronounced line width reduction and avoidance of undercutting.

[0018] It is an object of the present invention to provide a process for enhancing adhesion between copper and dielectric materials while still maintaining ultra-low roughness of the copper surface.

[0019] As a specific goal, adhesion performance was expressed as a minimum peel strength reduction after a Highly Accelerated Stress Test (HAST) should be achieved.

[0020] The object of the present invention is to reduce signal losses in high frequency product applications. Summary of the invention

[0021] The above object is achieved by an etching method for copper and copper alloy surfaces according to technical solution 1. Preferred embodiments of the invention can be found in the dependent claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Shows cross sections of various copper wires, depicting

[0023] a) Untreated copper wire ( Figure 1 A);

[0024] b) Copper wire with undercut formation ( Figure 1 B);

[0025] c) Copper wire with linear shape change ( Figure 1 C); and

[0026] d) Copper lines with reduced line width ( Figure 1 D).

[0027] exist Figure 1 In B, the copper line is marked as 1 and the undercut is marked as 2. It can be found that the undercut exists under the copper line. Figure 1 C depicts a copper line with undesirable linear shape variation. The copper line shown has a trapezoidal shape and the dashed line highlights the desired rectangular shape. Figure 1 D Display Figure 1 Untreated copper line (top) and treated copper line (bottom) of A with the line width reduction emphasized by the dashed line.

[0028] Figure 2 Shows SEM images of different samples.

[0029] Figure 3 FE-SEM surface morphology of copper surfaces treated with the pre-dip composition and etching solution (ED = 0.08 μm) is shown.

[0030] Figure 4 The surface roughness of (a) untreated and (b) treated copper surfaces by the method of the present invention is shown. An overview of the measured Sa, Sq, St and RSAI is shown in the upper left figure. The measurements were obtained by atomic force microscopy (AFM) at a 20×20 μm measurement window.

[0031] Figure 5 The zero line width of the ring conductor treated with the method of the present invention is shown to be reduced. No significant line width change occurs after treatment.

[0032] Figure 6 The copper removal mechanism is shown for: (a) the method of the present invention, where ED = 0.08 μm, and (b) a conventional adhesion enhancement process, where ED = 0.25 μm.

[0033] Figure 7 The adhesion performance evaluation in the form of peel strength for different dielectric materials is shown. In addition to the initial stage, the peel strength evaluation is also performed in the post-HAST stage. Material 1 is Ajinomoto GXT31 and the new material 2 is Ajinomoto GYXX. Other details are provided in the experimental section.

[0034] Figure 8 The evaluation of adhesion performance in the form of peel strength at different stages of the method of the present invention is presented. Material 1 (Ajinomoto GXT31) was used for the evaluation. Further details are provided in the experimental section.

[0035] Fig. 9 The signal integrity loss performance of the surface of the present method at 28 GHz is demonstrated compared to untreated and standard low roughened oxide replacement (OR) surfaces. A high performance low Dk dielectric material is stacked on the annular copper. DETAILED DESCRIPTION

[0036] Throughout this specification, unless otherwise stated, percentages are weight percentages (wt%). An exception is the yield, which is provided as a percentage of the theoretical yield. Unless otherwise stated, the concentrations provided in this specification refer to the volume of the entire solution.

[0037] The method for nanoetching copper or copper alloy surfaces is characterized by the following method steps:

[0038] i) providing a substrate having at least one copper or copper alloy surface,

[0039] ii) contacting at least a portion of the copper or copper alloy surface with a prepreg composition,

[0040] iii) contacting at least a portion of the copper or copper alloy surface with an etching solution,

[0041] The method is characterized in that

[0042] - the steps are performed sequentially;

[0043] - step ii) is a non-etching step;

[0044] - step iii) is an etching step; and

[0045] - the pre-dip composition comprises at least one sulfur-containing compound selected from the group consisting of:

[0046] a) Compounds of formula (I)

[0047]

[0048] in

[0049] X=S or S(O);

[0050] R 1 , R 2 , R 3 , R 4 =H, C1-C6 alkyl, OH,

[0051] Preferably, thiourea [X = S; R 1 , R 2 , R 3 , R 4 =H],

[0052] their derivatives, salts and mixtures thereof;

[0053] b) Compound of formula (II)

[0054]

[0055] in

[0056] X = S, S(O), SS;

[0057] R 1 , R 2 , R 3 =H, C1-C6 alkyl, OH or R 1 +R 3 =CH=CH,

[0058] R 5 =H, C1-C6 alkyl, OH,

[0059]

[0060] or R 3 +R 5 =CH=CH,

[0061] their derivatives, salts and mixtures thereof;

[0062] c) Structure YH or Y 2 Compounds (thiols or disulfides)

[0063] in

[0064] Where X = S,

[0065] R 6 =COOH, C1-C6 alkyl; R 7 =H, NH2, C1-C6 alkyl; R 8 =COOH, SO3H, C1-C3

[0066] Alkyl; and

[0067] d) 3-nitrobenzenesulfonic acid.

[0068] The steps are performed in the order presented above.

[0069] Step i) - Providing a substrate having at least one copper or copper alloy surface

[0070] In the context of the present invention, the substrate can be any substrate comprising a copper and copper alloy surface. The substrate can be made entirely of copper or a copper alloy, or it comprises a surface made of copper or a copper alloy. Preferably, the substrate is selected from copper foil, copper alloy foil, printed circuit board, IC substrate, interposer, copper-plated semiconductor wafer and copper-clad laminate (CCL). Copper-plated semiconductor wafer means a wafer substrate having copper or copper alloy structures (such as trenches, pipelines, spots, etc.) thereon.

[0071] As defined herein, the copper surface is preferably made of 99% by weight or more copper. The term "copper alloy" of the present invention preferably refers to an alloy consisting of 90% to 99% by weight copper. Preferably, the other components in the alloy are one or more selected from the following: boron, silicon, phosphorus or another metal such as nickel, iron, cadmium, zinc, tin, titanium.

[0072] Electrolytically deposited (ED) copper and copper alloy surfaces are particularly preferred, with an average grain size d 50 It is 1 to 5 μm of copper and copper alloy surfaces as determined by scanning electron microscopy (SEM).

[0073] Step ii) - contacting at least a portion of the copper or copper alloy surface with a prepreg composition

[0074] The method for treating a copper or copper alloy surface according to the present invention comprises step ii). This step ii) is performed between steps i) and iii).

[0075] As is known from the prior art, for example from WO 2017 / 108513, the etching process may optionally comprise a so-called pretreatment step of the copper or copper alloy surface: the pretreatment is carried out between steps i) and iii). Methods for pretreatment of copper and copper alloy surfaces are known in the art. Such pretreatments include, in particular, cleaning steps, removal of undesirable layers, such as chromate and / or oxide layers, and deposition of organic monolayers (e.g. monolayers of azole corrosion inhibitors, levelers or brightener compounds, which are usually used for electrolytic copper coatings).

[0076] Cleaning of copper and copper alloy surfaces can be achieved by various methods known in the art. Typically, such cleaning steps use aqueous solutions, which can be acidic or alkaline and optionally contain surfactants and / or cosolvents, such as glycols. The chromate layer can be removed by oxidative treatment using, for example, an aqueous solution containing sodium persulfate and / or other oxidants. The oxide layer or other undesirable residues on the copper or copper alloy surface can be removed by an acidic aqueous treatment. The organic monolayer can be formed by treating the copper or copper alloy surface with an aqueous solution containing an azole corrosion inhibitor, such as benzotriazole.

[0077] In contrast, in step ii) of the process of the present invention, the pre-dip composition comprises at least one sulphur-containing compound selected from the group consisting of several subgroups a) to d).

[0078] These subgroups a) to d) are described below.

[0079] According to the present invention, the term "alkyl" includes branched or non-branched alkyl, which includes cyclic and / or non-cyclic structural elements, wherein the cyclic structural elements of the alkyl naturally require at least 3 carbon atoms. According to the present invention, the term "C1-CX alkyl" refers to an alkyl with 1 to X carbon atoms. For example, C1-C6 alkyl especially includes methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, tert-pentyl, neopentyl and hexyl. In theory, substituted alkyl can be obtained by replacing at least one hydrogen with a functional group (such as amino, hydroxyl, mercaptan, alkoxy and sulfanyl). Preferably, the alkyl is not substituted or it is substituted by hydroxyl and / or amino.

[0080] The term "aryl" as used in the present specification and claims refers to a cyclic aromatic hydrocarbon residue, such as phenyl or naphthyl, in which individual ring carbon atoms may be replaced by N, O and / or S, such as benzothiazolyl. In addition, in various cases, the aryl residue may be substituted by replacing hydrogen with a functional group (e.g., amino, hydroxyl, thiol, alkoxy and sulfanyl). Preferably, the aryl group is unsubstituted or substituted by hydroxyl and / or amino.

[0081] The term "aralkyl" as used in the present specification and claims refers to a hydrocarbon residue composed of an alkyl group and an aryl group, such as benzyl and tolyl.

[0082] a) Compounds of formula (I)

[0083] Compound of formula (I)

[0084]

[0085] in

[0086] X=S or S(O);

[0087] R 1 , R 2 , R 3 , R 4 =H, C1-C6 alkyl, OH,

[0088] their derivatives, salts and mixtures thereof;

[0089] b) Compound of formula (II)

[0090] Compound of formula (II)

[0091]

[0092] in

[0093] X = S, S(O), SS;

[0094] R 1, R 2 , R 3 =H, C1-C6 alkyl, OH or R 1 +R 3 =CH=CH,

[0095] R 5 =H, C1-C6 alkyl, OH or R 3 +R 5 =CH=CH,

[0096]

[0097] their derivatives, salts and mixtures thereof;

[0098] Formulae (I) and (II) contain the same structural elements of formula (III):

[0099]

[0100] The dashed line in formula (III) indicates that one corresponding bond is a double bond, while the other bond is a single bond.

[0101] Other substituents at the N atom and possible X groups are not depicted.

[0102] This results in two possible structural elements: one possible structural element is one in which the double bond is between the carbon atom and the S atom of the group X; at the same time, the bond between the carbon atom and the second N atom is a single bond. This structural element is represented by formula (IV):

[0103]

[0104] Another possible structural element is one in which the double bond is between the carbon atom and the second N atom; at the same time, the bond between the carbon atom and the S atom of the group X is a single bond. This requires X to have at least one other substituent, which is also not depicted. This structural element is represented by formula (V):

[0105]

[0106] c) Structure YH or Y 2 Compounds (thiols or disulfides)

[0107] in

[0108] Where X = S

[0109] R 6 =COOH, C1-C6 alkyl; R 7 =H, NH2, C1-C6 alkyl; R 8 =COOH, SO3H, C1-C3

[0110] alkyl

[0111] their derivatives, salts and mixtures thereof;

[0112] d) 3-Nitrobenzenesulfonic acid

[0113] 3-Nitrobenzenesulfonic acid.

[0114] Step ii) is a non-etching step.

[0115] This means that no significant weight loss of the copper or copper alloy can be detected during step ii).

[0116] The weight loss is determined as follows. A "dry" disc is the weight before and after treatment. For a standard 15 cm x 7.5 cm plate, with copper on both sides, a weight difference of 10 mg relates to a 50 nm etch depth. 'No significant weight loss' means that the weight loss of the disc is 2 mg or less per disc, preferably 1 mg or less per disc.

[0117] The pH value of the predip composition according to the invention is preferably from -1 to 11.

[0118] When the pH is below 7, the pH is adjusted with at least one acid selected from inorganic acids and / or organic acids. Preferred acids are gluconic acid, sulfuric acid, formic acid, propionic acid and methanesulfonic acid (MSA).

[0119] When the pH value is higher than 7, the pH value is adjusted with at least one base selected from alkaline substances, preferably an inorganic alkali metal (KOH, NaOH), and most preferably NaOH.

[0120] In step ii) of the method of the present invention, the pre-dip composition comprises at least one sulfur-containing compound selected from the group consisting of several subgroups a) to d). The total concentration of the above-mentioned sulfur-containing compounds selected from the group consisting of several subgroups a) to d) is preferably in the range of 20 mg / l to 20 g / l, more preferably in the range of 50 mg / l to 10 g / l, and even more preferably in the range of 100 mg / l to 1 g / l.

[0121] The temperature of the pre-dip composition in step ii) is preferably in the range of 20 to 70°C, more preferably 20 to 55°C, even more preferably 30 to 55°C.

[0122] The contact time of the pre-dip composition with the copper or copper alloy surface must be adjusted with respect to the temperature of the pre-dip composition. The contact time of the pre-dip composition with the copper or copper alloy surface is generally in the range of 15 to 600 seconds, more preferably in the range of 15 to 300 seconds, and even more preferably in the range of 30 to 90 seconds.

[0123] Step iii) - contacting at least a portion of the copper or copper alloy surface with an etching solution

[0124] Step iii) is an etching step.

[0125] This means that by weight loss measurement, significant differences in copper and copper alloys before / after step iii) can be detected. The weight loss is determined as described previously. 'Significant weight loss' means that the weight loss of the disc is 1 mg per disc or more, preferably 5 mg per disc or more.

[0126] Etching solution

[0127] The etching solution comprises at least one oxidizing agent suitable for oxidizing copper. For the provided concentrations and pH values, the oxidizing agent suitable for oxidizing copper generally has a standard oxidation potential greater than that of copper. Typically, the concentration of the at least one oxidizing agent suitable for oxidizing copper is in the range of 0.05 to 20 wt %, preferably 1.0 to 10.0 wt % or 15 wt %.

[0128] Preferably, the at least one oxidizing agent is selected from the group consisting of: peroxides, such as hydrogen peroxide; metal peroxides, such as sodium peroxide, potassium peroxide; metal superoxides, such as potassium superoxide; copper ions and iron ions. To prevent the decomposition of peroxides, other additional compounds, such as p-phenolsulfonic acid, may be added. Peroxides and superoxides are preferably contained in a concentration in the range of 1 to 150 g / l.

[0129] The iron ions may be provided by any water-soluble iron ion source such as an iron (III) salt (i.e., a ferric salt) or an iron (III) complex. Preferably, the iron ion source is selected from the group consisting of: iron sulfate (Fe 2 (SO 4 ) 3 ), ferric chloride (FeCl 3 ), ferric bromide (FeBr 3 ), iron nitrate (Fe(NO 3 ) 3 ), ferrous acetate (Fe(OC(O)CH 3 ) 3 ), ferric hydroxide (Fe(OH) 3 ), its corresponding hydrate or a mixture of the foregoing substances. It preferably contains trivalent iron ions in a concentration ranging from 1 to 50 g / l.

[0130] The copper ions can be provided by any water-soluble copper ion source, such as a copper salt or a copper complex. Any water-soluble copper salt is a possible copper ion source, preferably the copper ion source is copper (II) sulfate, copper (II) chloride, copper (II) bromide, copper (II) acetate, copper (II) formate, copper (II) oxide, copper (II) hydroxide, alkyl copper (II) sulfonate, aryl copper (II) sulfonate, hydrate thereof or a mixture of the foregoing. Preferably the copper ions are contained in a concentration in the range of 1 to 70 g / l.

[0131] The at least one oxidizing agent may be selected from the group consisting of copper ions and iron ions. The etching solution may comprise at least one source of iron ions and at least one source of copper ions as oxidizing agents.

[0132] The etching solution comprises at least one acid. The at least one acid is preferably selected from the group consisting of sulfuric acid, alkylsulfonic acids (such as methanesulfonic acid), arylsulfonic acids (such as phenylsulfonic acid), toluenesulfonic acid, nitric acid, phosphoric acid, formic acid, acetic acid, propionic acid and mixtures thereof. More preferred are sulfuric acid, alkylsulfonic acids and arylsulfonic acids, because their high conductivity makes them extremely suitable for use in the case of regenerating the etching solution by electrolytic methods. The total concentration of the above-mentioned acids is preferably in the range of 10 to 250 g / L.

[0133] The etching solution optionally comprises at least one halide ion source. Preferably, a chloride ion source and a bromide ion source. Fluoride ions may form hydrofluoric acid in an acidic medium, which is highly toxic and difficult to handle, while iodide ions may be oxidized in the etching solution, rendering it ineffective. An example of a suitable chloride ion source is a water-soluble chloride salt. Preferably, the at least one chloride ion source is selected from the group consisting of hydrochloric acid, water-soluble metal chlorides (such as alkali metal chlorides, such as lithium chloride, sodium chloride, potassium chloride and cesium chloride), alkaline earth chlorides (such as manganese chloride, calcium chloride, strontium chloride and barium chloride), transition metal chlorides (such as manganese chloride, iron chloride, cobalt chloride, nickel chloride, copper chloride and zinc chloride), ammonium chloride and mixtures thereof. More preferably, the at least one chloride ion source is selected from the group consisting of hydrochloric acid, alkali metal chlorides and ammonium chloride. An example of a suitable bromide ion source is a water-soluble bromide salt. Preferably, the at least one bromide ion source is selected from the group consisting of: hydrobromic acid, water-soluble metal bromides (such as alkali metal bromides, such as lithium bromide, sodium bromide, potassium bromide and cesium bromide), alkaline earth bromides (such as manganese bromide, calcium bromide, strontium bromide and barium bromide), transition metal bromides (such as manganese bromide, iron bromide, cobalt bromide, nickel bromide, copper bromide and zinc bromide), ammonium bromide and mixtures thereof. More preferably, the at least one bromide ion source is selected from the group consisting of: hydrobromic acid, alkali metal bromides, ammonium bromide and zinc bromide. In a preferred embodiment of the present invention, the concentration of halide ions is 1 mg / l or more. In a more preferred embodiment of the present invention, the concentration of halide ions is 5 mg / l or more. If iron ions are used as the only oxidant, the concentration of all halide ions is preferably in the range of 1 to 500 mg / l, more preferably 10 to 200 mg / l and most preferably 20 to 100 mg / l. If peroxide or superoxide is used as the only oxidant, the concentration of all halide ions is preferably in the range of 1 to 50 mg / l, more preferably 5 to 30 mg / l. If copper ions are used as the only oxidant, the concentration of all halide ions is preferably in the range of 0.1 to 200 g / l, more preferably 1 to 100 g / l. Iron halide or copper halide as oxidant can also provide optional halide ions. Halide ions improve the etching results, so that undesirable etching of very thin copper wires (such as copper wires with a width of less than 10 μm) can be prevented and the linear shape changes are significantly smaller.

[0134] The etching solution optionally comprises at least one azole corrosion inhibitor selected from the group consisting of benzotriazole, 5-methylbenzotriazole, 1H-1,2,3-methylbenzotriazole, imidazole, 1H-1,2,3-triazole, 4-methylthiazole, 3-amino-1H-1,2,4-triazole, 1H-tetrazole, 5-methyl-1H-tetrazole, 5-phenyl-1H-tetrazole and 5-amino-1H-tetrazole. Preferably, the azole corrosion inhibitor is selected from 1H-tetrazole, 5-methyl-1H-tetrazole, 5-phenyl-1H-tetrazole and 5-amino-1H-tetrazole, because such tetrazole derivatives provide improved etching solution stability. Due to the formation of a protective azole layer, the addition of an azole corrosion inhibitor can advantageously reduce the corrosion of the metal surface to be treated, and sometimes it also reduces the formation of precipitates from the etching solution during use. Occasionally, after some copper is dissolved from the copper or copper alloy surface, a precipitate is formed, which limits the service life of the etching solution. If the etching solution comprises at least one azole corrosion inhibitor, the total concentration of the optional azole corrosion inhibitors is preferably in the range of 0.01 to 2.0 wt. %.

[0135] The etching solution optionally comprises at least one polyalkylene glycol compound, such as polyethylene glycol, polypropylene glycol, copolymers of polyethylene glycol and polypropylene glycol and derivatives thereof, which can improve the wettability of the copper or copper alloy surface to be treated and thus improve the etching properties of the etching solution according to the invention. If the etching solution comprises at least one polyalkylene compound, the total concentration of the optional polyalkylene compound in the etching solution is in the range of 100 to 2000 mg / l.

[0136] If the etching solution contains iron (III) as an oxidizing agent, it optionally additionally contains at least one source of ferrous ions. The ferrous ions may be provided by any water-soluble source of ferrous ions, such as an iron (II) salt (i.e., a ferrous salt) or an iron (II) complex. Preferably, the source of ferrous ions is selected from the group consisting of: ferrous sulfate (FeSO 4 ), ammonium ferrous sulfate ((NH 4 ) 2 Fe(SO 4 ) 2 ), ferrous chloride (FeCl 2 ), ferrous bromide (FeBr 2 ), ferrous nitrate (Fe(NO 3 ) 2 ), ferrous acetate (Fe(OC(O)CH 3 ) 2 ) and ferrous hydroxide (Fe(OH) 2) and its corresponding hydrate. Preferably, the optional ferrous ions are used in a concentration in the range of 1 to 50 g / l. When ferric ions are used as oxidizing agent and it is necessary to regenerate the etching solution, the use of the optional ferrous ions is particularly suitable.

[0137] The etching solution according to the invention is an aqueous solution. This means that the main solvent is water. Other solvents miscible with water may be added, such as polar solvents, including alcohols, glycols and glycol ethers. For ecologically benign characteristics, it is preferred to use only water (i.e., more than 99% by weight based on all solvents).

[0138] The pH value of the etching solution according to the invention is preferably ≤11, more preferably ≤7, even more preferably ≤4, most preferably ≤1.5. It is particularly preferred that the pH value of the etching solution according to the invention is ≤1.0.

[0139] The etching solution according to the invention can be prepared by dissolving all components in water. If solubility problems occur, pH regulators (such as acids and bases) can be used to increase the solubility of the components to be dissolved. It can also be prepared by providing a concentrate of the etching solution according to the invention, followed by dilution and / or mixing before use.

[0140] In one embodiment of the present invention, the etching solution is an aqueous solution comprising or consisting of:

[0141] a) at least one acid;

[0142] b) at least one oxidizing agent suitable for oxidizing copper;

[0143] c) optionally, at least one halide ion source;

[0144] d) at least one solvent, preferably water;

[0145] e) optionally, at least one azole corrosion inhibitor;

[0146] f) optionally, at least one polyalkylene compound; and

[0147] g) optionally, at least one source of ferrous ions,

[0148] The concentrations of the individual components are as defined above.

[0149] In a preferred embodiment of the present invention (referred to herein as a "ferric ion etching solution"), the etching solution is an aqueous solution comprising or consisting of:

[0150] a) at least one acid;

[0151] b) at least one source of ferric ions, preferably in a concentration ranging from 1 to 50 g / l;

[0152] c) at least one halide ion source;

[0153] d) at least one solvent, preferably water;

[0154] e) optionally, at least one azole corrosion inhibitor; and

[0155] f) Optionally, at least one polyalkylene compound.

[0156] In another preferred embodiment of the present invention (referred to herein as "copper ion etching solution"), the etching solution is an aqueous solution comprising or consisting of:

[0157] a) at least one acid;

[0158] b) at least one source of copper ions, preferably in a concentration in the range of 1 to 70 g / l;

[0159] c) at least one halide ion source;

[0160] d) at least one solvent, preferably water;

[0161] e) optionally, at least one azole corrosion inhibitor; and

[0162] f) Optionally, at least one polyalkylene compound.

[0163] In another preferred embodiment of the present invention, the etching solution is an aqueous solution comprising or consisting of:

[0164] a) at least one acid;

[0165] b) at least one oxidizing agent selected from the group consisting of peroxides and superoxides;

[0166] c) optionally, at least one halide ion source;

[0167] d) at least one solvent, preferably water;

[0168] e) optionally, at least one azole corrosion inhibitor; and

[0169] f) optionally, at least one polyalkylene compound,

[0170] The concentrations of the individual components are as defined above.

[0171] Etching solutions containing peroxides or superoxides as oxidizing agents are particularly suitable for roughening copper or copper alloy surfaces. Using the etching solution according to the invention, it is even possible to completely remove the seed layer in areas with a high conductor density.

[0172] According to the present invention, the etching solution can be used to etch copper and copper alloy surfaces, thereby allowing the organic substrate or final finish (such as immersion tin) to be tightly bonded to the copper or copper alloy surface or the organic substrate bonded thereto, while avoiding significant line shape changes, undercuts and line width reductions. Sufficient adhesion of the organic substrate to the final finish can thus be achieved.

[0173] Step iii) is also referred to herein as the "treatment step". Contacting at least a portion of the copper or copper alloy surface with the etching solution may be achieved by any method known in the art. Typically, the etching solution may be sprayed, wiped or otherwise applied to the copper or copper alloy surface, or the copper or copper alloy surface may be dipped or immersed in the etching solution. Preferably, the etching solution is sprayed onto the surface. Delivery of the etching solution to the surface is also improved and diffusion processes are minimized.

[0174] The etching solution can also be used in horizontal equipment, reel-to-reel, vertical and vertical conveyorized equipment.

[0175] The temperature of the etching solution in step iii) is preferably in the range of 20 to 50° C. The higher the temperature of the etching solution, the faster the etching process of the copper or copper alloy surface is caused. However, too high a temperature may be detrimental to the stability of the etching solution.

[0176] The contact time of the etching solution with the copper or copper alloy surface must be adjusted for the temperature of the etching solution and the desired etching depth. The contact time of the etching solution with the copper or copper alloy surface is generally in the range of 5 to 300 seconds. In some cases, the contact time needs to be adjusted for the desired etching result, such as when more copper is removed. This adjustment can be performed by routine experimentation as needed.

[0177] The method according to the present invention may include a rinsing step with a solvent (such as water) during each process step. In particular, after the copper or copper alloy surface is contacted with the etching solution, the copper or copper alloy surface is appropriately rinsed with water to remove any undesirable solution residues. The method according to the present invention may further include a drying step. For example, it is possible to rinse the copper or copper alloy surface with hot water after the treatment step, followed by drying with hot air or in an oven. Then, before any further treatment, the copper or copper alloy surface can be immersed or otherwise treated with a dilute acid solution (e.g., 10 wt % hydrochloric acid or 10 wt % sulfuric acid).

[0178] Other steps (optional)

[0179] The method for treating a copper or copper alloy surface according to the present invention optionally further comprises the following steps

[0180] iv) contacting the copper or copper alloy surface with a post-impregnation solution.

[0181] This step is called the "post-impregnation step".

[0182] An optional step iv) (post-immersion step) is included in the method for treating the copper or copper alloy surface according to the invention after step iii) (treatment step). The contact of the copper or copper alloy surface with the post-immersion substance is selected from the same possibilities as provided for the contact between the etching solution and the copper or copper alloy surface in step iii). The same or different contact possibilities can be selected. If a post-immersion step is performed, it is advantageous to thoroughly rinse the copper or copper alloy surface or otherwise remove any residues before applying the photoresist or solder mask.

[0183] Various post-impregnation solutions can be used. In the following, several categories are described. The corresponding names describe the main features. However, combinations of these features are also possible.

[0184] The acidic post-dip solution is an aqueous solution containing at least one acid, preferably hydrochloric acid. The pH of the acidic post-dip material is generally 1 or less. If cupric chloride is used as the oxidizing agent in the etching solution, then an acidic post-dip material is generally used. Alternatively, if a photoresist is applied subsequently or at a later stage of the method according to the invention, then an acidic post-dip material can be used, because photoresists are unstable to alkaline treatments or such alkaline residues present on the surface on which such photoresists are to be deposited.

[0185] The alkaline post-impregnation solution contains at least one hydroxide ion (OH - ) source. Such a source of hydroxide ions may be any water-soluble compound which releases or otherwise forms hydroxide ions when in contact with water, such as a base. Preferably, the source of hydroxide ions is selected from metal hydroxides (such as alkali metal hydroxides) and amines (such as ammonia). The pH of the alkaline post-dip solution is typically 10 or higher. An alkaline post-dip solution is optionally used if a solder mask is applied subsequently or at any later stage (because the solder mask is unstable to acidic treatments, acidic residues on the surface on which such a solder mask will be deposited) or if an oxidant other than copper ions is present in the etching solution.

[0186] The organic post-dip solution comprises at least one organic molecule, such as an organic molecule disclosed in EP2020 / 055192 and / or EP2019 / 061526, which are incorporated herein by reference. It has been found that the organic post-dip solution can have various advantages, such as anti-discoloration effect, enhanced adhesion to resin materials (e.g., for permanent adhesion or for solder resist) and / or increased darkening effect.

[0187] The method for treating a copper or copper alloy surface according to the present invention optionally further comprises the following step v) laminating an organic matrix onto the treated copper or copper alloy surface.

[0188] Organic matrices include (but are not limited to) prepregs, epoxy curing agents, solder masks, photoresists, etc. Prepregs are fiber reinforced plastics, typically using glass reinforced epoxy matrices such as FR-4, FR-5, and a range of build-up films (e.g., Ajinomoto GX92, Ajinomoto GXT31).

[0189] In the method according to the present invention, instead of step v) or in addition to step v), the following steps may be included:

[0190] vi) depositing a final finish on the treated copper or copper alloy surface or portion thereof.

[0191] The final finish includes immersion tin, electroless nickel immersion gold (ENIG), electroless nickel electroless palladium electrodeless gold (ENEPIG), electroless palladium electrodeless gold (EPIG), immersion silver, organic solder preservative (OSP), etc. These finishes are well-known in the art. Suitable tin deposition methods include, for example, immersion tin coating, as described in EP 2476779 B1.

[0192] Advantageously, the method according to the present invention causes little or no degradation of line shape because little or no copper is dissolved from the sides of the copper trenches and lines.

[0193] The following describes different objectives of the method of the present invention and methods for achieving them.

[0194] Surface morphology

[0195] The method according to the present invention produces pits in a copper or copper alloy surface, wherein a plurality of the pits are at an obtuse angle relative to the top surface, and a depth of the plurality of pits is at least 50 nm and less than 500 nm.

[0196] After step ii) and step iii) of the method of the present invention, the morphology of different copper surfaces was observed by FE-SEM. The results are shown in Figure 3 middle.

[0197] After step ii), the DC surface shows an extremely smooth surface profile and visible polycrystalline copper grain size. The islands of different grain sizes are evenly distributed along the surface ( Figure 3 , upper left).

[0198] Similar surface profiles were observed on the ring-shaped samples ( Figure 3 , lower left).

[0199] After step iii), by etching chemistry, pits with shallower depth are produced by copper removal. Copper removal (trench etching) in the z direction is carried out along the island boundaries of copper grains, which have been previously detected in the pre-impregnation treatment surface. The indication of the preferred side for copper removal by etching is the grain boundary. According to current advanced technology, the grain boundary of copper can act as a reservoir and transport pathway for site defects caused by corrosive chemicals. This may be an effective phenomenon occurring on the copper surface in etching chemistry. Therefore, after treatment with an etching solution, a morphology containing nano-sized pits is obtained on the copper surface.

[0200] Ultra low roughness

[0201] The main goal of the process of the present invention is to enhance the adhesion between copper and dielectric materials while still maintaining ultra-low roughness of the copper surface. Coupling of roughness measurements was performed to measure the increase in surface roughness caused by the process of the present invention. Atomic force microscopy (AFM) was used as the method of choice because of its high resolution in measuring surface roughness at the nanometer scale. Figure 4 It can be found that Sa, Sq and St measured in AFM of the copper surface show only a small increase caused by the treatment according to the method of the invention compared to the untreated surface.

[0202] The corresponding measure is:

[0203] Sa: average surface roughness;

[0204] Sq: Root mean square roughness

[0205] St: Peak-Peak

[0206] RSAI: Relevant Surface Area Increase.

[0207] In contrast, the measured relative surface area increase (RSAI %) of surfaces treated with the method of the present invention showed a significant increase of up to 40% over untreated surfaces.

[0208] The method of the present invention produces a surface that exhibits nanostructures rather than microstructures. Thus, the desired ultra-low roughness of the copper surface is achieved by the method of the present invention.

[0209] In the method of the present invention, the substrate comprising a copper or copper alloy surface is preferably selected from the group consisting of copper foil, copper alloy foil, printed circuit board, IC substrate, interposer, copper plated semiconductor wafer and copper clad laminate.

[0210] In a preferred embodiment, a method for creating recesses in a copper or copper alloy surface is provided.

[0211] In a more preferred embodiment, the plurality of recesses are at an obtuse angle relative to the top surface.

[0212] In another more preferred embodiment, the depth of the plurality of recesses is at least 50 nm and less than 500 nm.

[0213] The article having a copper or copper alloy surface is preferably a patterned sample.

[0214] In the method of the present invention, the size of the pattern changes less than 10% of the original value, preferably the size of the pattern changes less than 7% of the original value, more preferably the size of the pattern changes less than 5% of the original value, and most preferably the size of the pattern does not change.

[0215] In a specific embodiment, the dimensional change is a reduction in line width.

[0216] Therefore, in a preferred method of the present invention, the line width reduction is less than 10% of the original value, preferably the line width reduction is less than 7% of the original value, more preferably the line width reduction is less than 5% of the original value, and most preferably the line width reduction is 0% of the original value.

[0217] like Figure 5 As shown in , the dimensions (L / S) of all the copper rings did not change significantly compared to the untreated state. Figure 5 In the left part of FIG. 1 , it is clear that a significant reduction in line width occurs when using a conventional adhesion enhancement process. The reduction is even further exacerbated when processing smaller dimensions in this process.

[0218] Without wishing to be bound by any particular theory or explanation, the following are assumed:

[0219] To explain the above phenomenon, we must first understand the differences between the processes in the mechanisms used to remove copper from the surface ( Figure 6 ). The key to copper etching technology is the use of oxidants (strong oxidants), dissolving agents (acids and / or solvents) and etching additives. The optimal combination of these components will determine both the copper removal rate and the preferred reaction sites on the surface. The basic chemical composition of conventional etching processes is usually designed to react with the copper surface in all sites, rather than selectively removing ( Figure 6 b). In addition to arcing the copper grain boundaries as weak points, the copper grains are also loaded with chemicals. Etching down the recesses of the underlying copper layer is enhanced. Therefore, excessive line width reduction inevitably occurs. Compared with conventional etching processes, step (iii) in the method of the present invention hinders arcing of copper grains. Dislocation sites in grain boundaries are preferentially dissolved. Therefore, roughness on the surface can be formed without reducing line width.

[0220] Adhesion performance

[0221] The adhesion between copper and dielectric materials was evaluated by peel strength test. The unit of measurement is N / cm. Despite the ultra-low roughness characteristics, the copper foil treated by the method of the present invention exhibits very good adhesion on different dielectric materials ( Figure 7 ).

[0222] Just after lamination (initial), the peel strength of the samples treated with the method of the present invention is similar to that of the untreated samples. This is valid for both dielectric materials. The peel strengths of material 1 (Ajinomoto GXT31) and new material 2 (Ajinomoto GYXX) are approximately 8 N / cm and 6 N / cm, respectively. The significant difference in peel strength forces indicates a change in material properties. In the Highly Accelerated Stress Test (HAST), the samples were subjected to moisture penetration at the copper / dielectric interface. The subsequent peel strength degradation was mainly caused by water molecules in the humid oven chamber. At the weak interfacial bonds of the copper / dielectric material, the infiltrated water molecules replace the bonds due to the higher interaction energy of water with the copper surface. This can Figure 7 It was found in the figure (untreated surface) that the peel strength after HAST deteriorated significantly, from 7.8 N / cm (initial) to 3.1 N / cm (after HAST) and from 6 N / cm (initial) to 2.9 N / cm (after HAST) for material 1 and new material 2, respectively.

[0223] Thanks to the mechanical anchoring caused by the nanostructures produced in step iii) of the method of the present invention and the chemical bonding produced by the pre-coating and coating, the samples incorporating the method of the present invention can withstand the HAST test with only a slight reduction in peel strength after the test. The strong interfacial bonds of the copper / dielectric material hinder the adverse effect of water molecule penetration at the interface.

[0224] In order to distinguish the different contributions of the mechanisms to adhesion enhancement, a collection of samples was prepared for peel strength testing. To minimize data interpretation issues, only Material 1 was used for evaluation. The dielectric material was laminated with the copper foil in each sequential step of the process of the present invention, and the initial and post-HAST peel strength data are presented in Figure 8. Similar to the peel strength data observed previously, there is no significant difference in the test samples just after lamination (initial). For the post-HAST peel strength, only the samples treated with pre-impregnation show the most reduction. This means that if a method with steps i) and ii) but without step iii) is performed, the reduction is most obvious. In contrast, if the method is performed according to the present invention, i.e., comprising all steps i) to iii), the post-HAST peel strength is improved by 40%. This shows that the nanostructure formation on the surface in step iii) has a major contribution to adhesion enhancement. However, when the sample is then treated by pre-coating and coating, i.e., additionally comprising step iv), wherein the post-impregnation solution is an organic post-impregnation solution, the peel strength is further increased by 67%.

[0225] Low signal loss of the method of the present invention

[0226] One of the main goals of the ultra-low roughness adhesion enhancement system is to reduce signal loss in high frequency product applications. Therefore, further testing was performed to measure signal insertion loss at a high frequency bandwidth. In this case, the frequency applied in the test was 28 GHz. Samples of stacked assemblies were produced using low Df dielectric materials and copper treated with the method of the present invention. At the same time, other samples of untreated copper and low roughness oxide replacement (OR) were also included for benchmark analysis of performance ( Fig. 9 ).

[0227] The ultra-low roughness characteristic of the method of the present invention has a significant advantage in the insertion loss performance at high frequencies. Compared to the low roughness OR, the insertion loss is significantly reduced by about 2%. This is attributed to the ultra-low roughness produced by the process. The degree of difference between the method of the present invention and the untreated sample is minimal. This confirms that the ultra-low roughness of the method of the present invention is fully utilized in high frequency substrate applications.

[0228] Example

[0229] A. A method for nano-etching a copper or copper alloy surface, characterized by the following method steps:

[0230] i) providing a substrate having at least one copper or copper alloy surface,

[0231] ii) contacting at least a portion of the copper or copper alloy surface with a prepreg composition,

[0232] iii) contacting at least a portion of the copper or copper alloy surface with an etching solution,

[0233] The method is characterized in that

[0234] - the steps are performed sequentially;

[0235] - step ii) is a non-etching step;

[0236] - step iii) is an etching step; and

[0237] - the pre-dip composition comprises at least one sulfur-containing compound selected from the group consisting of:

[0238] a) Compounds of formula (I)

[0239]

[0240] in

[0241] X=S or S(O);

[0242] R 1 , R 2 , R 3 , R 4 =H, C1-C6 alkyl, OH,

[0243] their derivatives, salts and mixtures thereof;

[0244] b) Compound of formula (II)

[0245]

[0246] in

[0247] X = S, S(O), SS;

[0248] R 1 , R 2 , R 3 =H, C1-C6 alkyl, OH or R 1 +R 3 =CH=CH,

[0249] R 5 =H, C1-C6 alkyl, OH or R 3 +R 5 =CH=CH

[0250]

[0251] their derivatives, salts and mixtures thereof;

[0252] c) Structure YH or Y 2 Compounds (thiols or disulfides)

[0253] in

[0254] Where X = S,

[0255] R 6 =COOH, C1-C6 alkyl; R7 =H, NH2, C1-C6 alkyl; R 8 =COOH, SO3H, C1-C3

[0256] Alkyl, and

[0257] d) 3-nitrobenzenesulfonic acid.

[0258] B. The method according to embodiment A, wherein the at least one sulfur-containing compound is selected from the group consisting of:

[0259] a) Thiourea [X = S; R 1 , R 2 , R 3 , R 4 =H],

[0260] b) 2-aminothiazole [X = S, R 1 , R 2 =H, R 3 +R 5 :-CH=CH-], 2-mercaptoimidazole [X=S, R 2 , R 5 =H, R 1 +R 3 :-CH=CH-], disulfide formamidine (dihydrochloride) (X=SS, R 1 , R 2 , R 3 =H, R 5 = Formamidinesulfinic acid [X=S(O), R 1 , R 2 , R 3 =H, R 5 =OH], derivatives, salts and mixtures thereof; and

[0261] c) Cysteine ​​[X = SH, R1 = H, R2 = NH2, R3 = COOH], 3,3'-dithiodipropionic acid [X = SS, R1 = H; R2 = H; R3 = COOH].

[0262] C. The method according to embodiment A or B, wherein in step ii), the pre-dip composition is an aqueous solution with a pH value of -1 to 11.

[0263] D. The method according to any one of the preceding embodiments, wherein in step iii), the etching solution is an aqueous solution comprising or consisting of:

[0264] a) at least one acid;

[0265] b) at least one oxidizing agent suitable for oxidizing copper; preferably, the at least one oxidizing agent is selected from the group consisting of peroxides and superoxides;

[0266] c) optionally, at least one halide ion source;

[0267] d) at least one solvent, preferably water;

[0268] e) optionally, at least one azole corrosion inhibitor;

[0269] f) optionally, at least one polyalkylene compound; and

[0270] g) If the at least one oxidizing agent comprises Fe(III), optionally at least one source of ferrous ions is included.

[0271] E. The method according to any one of the preceding embodiments, further comprising the following steps

[0272] iv) contacting the copper or copper alloy surface with a post-impregnation solution.

[0273] F. A method according to any of the preceding embodiments, characterized in that the substrate comprising a copper or copper alloy surface is selected from copper foil, copper alloy foil, printed circuit board, IC substrate, interposer, copper plated semiconductor wafer and copper clad laminate.

[0274] G. A method according to any one of the preceding embodiments for producing recesses in a copper or copper alloy surface,

[0275] The plurality of recesses are formed at an obtuse angle relative to the top surface, and a depth of the plurality of recesses is at least 50 nm and less than 500 nm.

[0276] H. The method of embodiment G for treating an article having a copper or copper alloy surface, wherein the article is a patterned sample.

[0277] I. A method according to Example H, wherein the size of the pattern changes by less than 10% of the original value, preferably the size of the pattern changes by less than 7% of the original value, more preferably the size of the pattern changes by less than 5% of the original value, and most preferably the size of the pattern does not change.

[0278] J. A method according to embodiment I, wherein the dimensional change is a reduction in line width and the line width reduction is less than 10% of the original value, preferably the line width reduction is less than 7% of the original value, more preferably the line width reduction is less than 5% of the original value, and most preferably the line width reduction is 0% of the original value.

[0279] K. An article comprising a copper or copper alloy surface produced by the method according to any of the preceding embodiments, wherein one of the copper surfaces comprises recesses in the copper surface,

[0280] The plurality of recesses are formed at an obtuse angle relative to the top surface, and a depth of the plurality of recesses is at least 50 nm and less than 500 nm.

[0281] L. An article having a copper surface according to embodiment K, wherein the article is a patterned sample.

[0282] M. An article according to embodiment L, wherein the size of the pattern changes by less than 10% of the original value, preferably the size of the pattern changes by less than 7% of the original value, more preferably the size of the pattern changes by less than 5% of the original value, and most preferably the size of the pattern does not change.

[0283] N. An article according to embodiment M, wherein the dimensional change is a reduction in line width and the line width reduction is less than 10% of the original value, preferably the line width reduction is less than 7% of the original value, more preferably the line width reduction is less than 5% of the original value, and most preferably the line width reduction is 0% of the original value.

[0284] O. Use of the article according to any one of technical solutions K to N for temporary adhesive applications and / or permanent adhesive applications, and / or as a solder resist pretreatment and as a laser guided drilling (LDD) pretreatment.

[0285] P. According to the use described in technical solution O, it is used in a metal mesh touch screen.

[0286] The following non-limiting examples further illustrate the present invention.

[0287] Examples

[0288] The predip composition is prepared by dissolving all components in water or, if desired, in a dilute acidified or alkaline solution.

[0289] The etching solution was prepared by dissolving all components in water or in a dilute acidified solution as required.The average grain size of the electrodeposited (ED) copper foil used in the experiments was 0.5-3 μm as determined by SEM of electropolished samples.

[0290] The adhesion strength value (also called peel strength value) between the treated copper surface and the organic substrate was measured according to the method described in IPC-TM-650 Test Methods Manual No. 2.4.8 Revision C.

[0291] The images were acquired by scanning atomic force microscope (Digital Instruments) equipped with a The smoothness (or roughness) of the outer surface was measured using a NanoScope with a tip radius less than 7 nm, with a scan size of 20 × 20 μm and scanning in tapping mode. From these measurements, RSAI values ​​(relative surface area increase) and S a (average roughness) and are provided together with the corresponding examples below.

[0292] Microscopic characterization of the copper surface was performed using a Carl Zeiss SMT Ltd. EVO15-07.05 or Helios NanoLab 650 scanning electron microscope (SEM, FEI Company). Alternatively, an optical microscope (Olympus Optical Ltd., BX 60F-3) was used when appropriate.

[0293] To assess linear shape change (and therefore retention of the desired rectangular shape), the top-to-bottom difference was measured. 顶部 ) and bottom (width 底部 ) to obtain the top-bottom difference. The top-bottom difference is obtained by the following formula:

[0294] Top-Bottom Difference = Width 顶部 -width 底部

[0295] Thus, a negative top-bottom differential refers to a copper line that is etched primarily at the top, while a positive top-bottom differential refers to etching primarily at the bottom of the copper line. The top-bottom differential of the processed copper line should be nearly zero, whereby the copper line has a rectangular shape.

[0296] The line width reduction is obtained by measuring the copper line dimensions before and after treatment. The smaller the value, the better.

[0297] The etch rate is obtained by treating the copper clad laminate for 60 seconds and measuring the mass before and after etching. The difference can be recalculated for the 60 second etch rate.

[0298] Comparative is sometimes referred to herein as comp. and inventive as inv.

[0299] Structures for screening

[0300] Pre-preg composition

[0301]

[0302] Etching solution

[0303]

[0304]

[0305] *) The indicated additives are commercial products from Atotech Deutschland GmbH & Co. KG

[0306] **) Information not shown, e.g. on a technical data sheet

[0307] Experimental table

[0308]

[0309]

[0310] The corresponding SEM images are shown in Figure 2 middle.

Claims

1. A method for nano-etching a copper or copper alloy surface, characterized in that The following method steps: i) providing a substrate having at least one copper or copper alloy surface, ii) contacting at least a portion of the copper or copper alloy surface with a prepreg composition, iii) contacting at least a portion of the copper or copper alloy surface with an etching solution, The method is characterized in that - the steps are performed sequentially; - step ii) is a non-etching step; - step iii) is an etching step; as well as - the pre-dip composition comprises at least one sulfur-containing compound selected from the group consisting of: a) Compounds of formula (I) in X=S or S(O); R 1 , R 2 , R 3 , R 4 =H, C1-C6 alkyl, OH, their derivatives, salts and mixtures thereof; b) Compound of formula (II) in X = S, S(O), SS; R 1 , R 2 , R 3 =H, C1-C6 alkyl, OH, or R 1 +R 3 =CH=CH, R 5 =H, C1-C6 alkyl, OH, or R 3 +R 5 =CH=CH, their derivatives, salts and mixtures thereof; c) Compounds of structure YH or Y2 (thiol or disulfide) in Where X = S, R 6 =COOH, C1-C6 alkyl; R 7 =H, NH2, C1-C6 alkyl; R 8 =COOH, SO3H, C1-C3 alkyl, and d) 3-nitrobenzenesulfonic acid.

2. The method of claim 1, wherein the at least one sulfur-containing compound is selected from the group consisting of: a) Thiourea [X = S; R 1 , R 2 , R 3 , R 4 =H], b) 2-aminothiazole [X = S, R 1 , R 2 =H, R 3 +R 5 :-CH=CH-], 2-mercaptoimidazole [X=S, R 2 , R 5 =H, R 1 +R 3 :-CH=CH-], disulfide formamidine (dihydrochloride) (X=SS, R 1 , R 2 , R 3 =H, R 5 = Formamidinesulfinic acid [X=S(O), R 1 , R 2 , R 3 =H, R 5 =OH], derivatives, salts and mixtures thereof; and c) Cysteine ​​[X = SH, R1 = H, R2 = NH2, R3 = COOH], 3,3'-dithiodipropionic acid [X = SS, R1 = H; R2 = H; R3 = COOH].

3. The method according to any one of the preceding claims, wherein in step iii), the etching solution is an aqueous solution comprising or consisting of: a) at least one acid; b) at least one oxidizing agent suitable for oxidizing copper; preferably, the at least one oxidizing agent is selected from the group consisting of peroxides and superoxides; c) optionally, at least one halide ion source; d) at least one solvent, preferably water; e) optionally, at least one azole corrosion inhibitor; f) optionally, at least one polyalkylene compound; and g) If the at least one oxidizing agent comprises Fe(III), optionally at least one source of ferrous ions is included.

4. The method according to any one of the preceding claims, further comprising the steps of: iv) contacting the copper or copper alloy surface with a post-impregnation solution.

5. A method according to any one of the preceding claims, characterised in that The substrate comprising a copper or copper alloy surface is selected from the group consisting of copper foil, copper alloy foil, printed circuit board, IC substrate, interposer, copper plated semiconductor wafer and copper clad laminate.

6. The method according to any one of the preceding claims, for producing recesses in the copper or copper alloy surface, The plurality of recesses are formed at an obtuse angle relative to the top surface, and the depth of the plurality of recesses is at least 50 nm and less than 500 nm.

7. The method according to claim 6, which is used to treat an article having a copper or copper alloy surface, wherein the article is a patterned sample.

8. The method according to claim 7, wherein the size of the pattern changes by less than 10% of the original value, preferably the size of the pattern changes by less than 7% of the original value, more preferably the size of the pattern changes by less than 5% of the original value, and most preferably the size of the pattern does not change.

9. The method according to claim 8, wherein the dimensional change is a reduction in line width and the line width reduction is less than 10% of the original value, preferably the line width reduction is less than 7% of the original value, more preferably the line width reduction is less than 5% of the original value, and most preferably the line width reduction is 0% of the original value.

10. An article comprising a copper or copper alloy surface produced by the method according to any one of the preceding claims, wherein the copper surface comprises recesses in the copper surface, The plurality of recesses are formed at an obtuse angle relative to the top surface, and the depth of the plurality of recesses is at least 50 nm and less than 500 nm.

11. An article having a copper surface according to claim 10, wherein the article is a patterned sample.

12. The article according to claim 11, wherein the size of the pattern changes by less than 10% of the original value, preferably the size of the pattern changes by less than 7% of the original value, more preferably the size of the pattern changes by less than 5% of the original value, and most preferably the size of the pattern does not change.

13. The article according to claim 12, wherein the dimensional change is a reduction in line width and the line width reduction is less than 10% of the original value, preferably the line width reduction is less than 7% of the original value, more preferably the line width reduction is less than 5% of the original value, and most preferably the line width reduction is 0% of the original value.

14. Use of an article according to any one of claims 10 to 13 for temporary and / or permanent adhesive applications and / or as a solder resist pretreatment and as a laser guided drilling (LDD) pretreatment.

15. The use according to claim 14, which is used in a metal mesh touch screen.